VISITORS TO THE CITY OF ÉVORA: WHO ARE THEY? - Serra, Jaime Manuel Moleiro (2012)
Nowadays, driven by multiple factors, tourist demand presents patterned behaviour which is subdivided into several typologies according to destination, product consumed and visitor profile features. In the case of cultural tourism, a good example is that of historic cities, which have their own cultural identity and heritage, and compete to make themselves different from one another through many marketing strategies. This study presents the profile of visitors to the World Heritage City of Évora, including their travel motivations and level of satisfaction with the attributes. Subsequently, the main purpose of this study is to determine the cultural profile of visitors to the World Heritage City of Évora. The data collection technique applied was a visitor survey. The process adopted for the sample definition was a probabilistic sampling, namely the adoption of a stratified sampling plan, by place of residence. Further analysis shows that the most important motivations for visitors in selecting Évora are leisure, heritage/monuments and having a new cultural experience. However they indicate the fact that Évora is considered World Heritage City by UNESCO did influence the decision to visit this destination. Several findings provide the opportunity to establish adequate managerial and marketing strategies to suit the needs of the visitors.